Case Report: Durable Response to Very Low Dose Tyrosine Kinase Inhibitors in Advanced Hepatocellular Carcinoma - Tang, Tin-Yun; Daunov, Katherine; Lee, Richard T. (Frontiers in Oncology, 2021)
The oral tyrosine kinase inhibitors (TKI) sorafenib, regorafenib, and cabozantinib are approved for advanced hepatocellular carcinoma (aHCC) and improve survival. However, patients on these medications frequently require dose reductions or discontinuation due to multiple side effects leading to poor tolerability. Here we report three different aHCC patients with clinical responses outlasting those reported in their corresponding Phase 3 clinical trials on 1/8th the target dose for sorafenib, 1/4th the target dose for regorafenib and 1/6th the target dose for cabozantinib respectively. As these doses are below the minimal recommended doses on the FDA labels, this case series provides a preliminary demonstration that low dose TKI therapy can be effective and patients on TKIs should first assess for clinical response before empirically discontinuing TKI therapy on the basis of tolerating only a low dose.